Method for preparing ceramic material by electric field-dynamic pressure field coupling super-fast sintering

CN122897688APending Publication Date: 2026-10-13UNIV OF SCI & TECH BEIJING
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611129982.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-28
Publication Date
2026-10-13

AI Technical Summary

Technical Problem

然而,传统陶瓷制备工艺面临烧结致密化困难与微观结构精准调控受限等瓶颈问题:一方面,为实现充分致密化,通常需要较高的烧结温度与较长的保温时间,该条件诱发晶粒异常长大;另一方面,即便在静态压力作用下,残余气孔仍难以完全消除,致使材料致密度难以进一步提升,进而制约了陶瓷材料的宏观力学性能

Benefits of technology

本发明提供了一种陶瓷材料的制备方法,关键创新在于采用振荡压力与超快速烧结耦合的烧结策略,在一定程度上改变了陶瓷材料的致密化路径及组织演化机制。该烧结方式能够较短时间内同步实现陶瓷材料的致密化与抑制晶粒长大,并有利于引入和保留较多晶格缺陷及特殊微结构,从而实现材料性能的显著提升。采用本发明方法制得的陶瓷材料,相对密度≥97%,显微维氏硬度均有所提升。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122897688A_ABST
    Figure CN122897688A_ABST
Patent Text Reader

Abstract

The application provides a method for preparing a ceramic material by electric field-dynamic pressure field coupling ultrafast sintering, and belongs to the technical field of ceramic preparation. The method comprises the following steps: after ceramic powder is filled in a sintering mold, the sintering mold is placed in a rapid hot-pressing sintering device, short-time rapid sintering is carried out under a vacuum condition, the sintering mold is rapidly heated by an electric current, and ultrafast temperature rising is realized; when the temperature reaches a target sintering temperature and the pressure is stable, a dynamic oscillation force field is started, and the ceramic material is obtained after sintering is completed. Through the synergistic effect of the electric field-dynamic pressure field, the ceramic is densified in an extremely short total sintering time, the grain growth is effectively inhibited, the unique effect of the dynamic pressure significantly increases the internal stacking faults and other micro defects of the material, and the hardness, the fracture toughness and the bending strength of the ceramic material are significantly improved. The relative density and the mechanical properties of the ceramic material prepared by the method are far superior to those of a traditional static pressure sintering process.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of ceramic preparation technology, specifically relating to a method for preparing ceramic materials by ultra-fast sintering coupled with an electric field and a dynamic pressure field. Background Technology

[0002] Ceramic materials possess outstanding properties such as high hardness, high melting point, excellent corrosion resistance, and good thermal conductivity, leading to their widespread application in aerospace, nuclear engineering, semiconductor devices, and extreme environment protection. However, traditional ceramic manufacturing processes face bottlenecks such as difficulties in sintering densification and limitations in precise microstructure control. On the one hand, achieving sufficient densification typically requires high sintering temperatures and long holding times, conditions that induce abnormal grain growth. On the other hand, even under static pressure, residual pores are difficult to completely eliminate, hindering further increases in material density and thus limiting the macroscopic mechanical properties of ceramic materials. Furthermore, in traditional slow-heating sintering processes, the material system has ample time to evolve towards thermodynamic equilibrium, often making it difficult to form or retain special non-equilibrium microstructures, thus limiting the ability to precisely control the microstructure of ceramic materials.

[0003] In recent years, flash sintering has attracted widespread attention due to its significant improvement in sintering efficiency and potential reduction in energy consumption. Flash sintering achieves rapid densification of ceramics at lower temperatures and in shorter time periods by using a transient high electric field or by utilizing the rapid change in the material's conductivity with temperature. While this process can significantly reduce sintering temperature, shorten sintering time, and inhibit grain growth, it also presents significant technical challenges and limitations. Limited flash sintering is often accompanied by localized overheating, leading to uneven heat generation within the material, resulting in problems such as cracks, thermal stress concentration, and abnormal microstructure changes, leading to poor material uniformity and structural stability. Furthermore, flash sintering depends on the conductivity of the system; most ceramic materials have poor conductivity, limiting the application range of flash sintering. Moreover, applying a strong electric field or high current directly to the sample during flash sintering can cause undesirable chemical reactions or localized ablation at the electrode-material interface, thus affecting the overall performance of the material.

[0004] Taking boron carbide (B4C) ceramics as an example, B4C ceramics combine outstanding characteristics such as low density, high hardness, excellent corrosion resistance, high melting point, high wear resistance, good thermal shock resistance, stable chemical properties, and neutron absorption capacity. These characteristics make it show broad application prospects in the field of bulletproofing: its ultra-high hardness can effectively resist the impact of shrapnel; its density is only 2.52 g / cm³. 3Its chemical stability is far lower than that of common metallic protective materials; at the same time, its excellent chemical stability and neutron absorption capacity endow B4C ballistic shielding components with good nuclear radiation shielding performance. These combined advantages make B4C ceramics of significant application value in extreme service environments such as aerospace, nuclear protection, and military protection.

[0005] B4C, a compound dominated by covalent bonds (over 90%), has an extremely high melting point and weak self-diffusion ability, making it difficult to achieve high-density sintering of pure B4C ceramics. Furthermore, this material faces the bottleneck of difficult sintering. Currently, there are various sintering methods for pure B4C ceramics. Pressureless sintering typically requires sintering temperatures as high as 2200 °C and long holding times, easily leading to abnormal grain growth, resulting in unsatisfactory mechanical properties and poor density. Hot pressing, assisted by a static force field, can lower the sintering temperature to some extent and significantly improve the material density, but due to the still long high-temperature holding time, grain growth is severe, limiting the improvement in mechanical properties. While spark plasma sintering can achieve material densification and suppress significant grain growth through rapid heating and short holding times, this process struggles to effectively control microscopic defects, thus limiting the improvement of the material's mechanical properties. Meanwhile, existing rapid sintering technologies focus more on shortening sintering time and increasing density, but lack effective solutions for how to induce and retain non-equilibrium microstructures through rapid heating processes, and how to further enhance this effect through external field synergy.

[0006] Therefore, developing a process-controllable and structurally designable method for preparing high-performance ceramic materials is of great significance. This method, through synergistic optimization of sintering processes and micro-control, ensures both high densification and fine-grained structure of the material, while effectively controlling microscopic defects and microstructure evolution, thereby macroscopically improving the mechanical properties of the ceramic material. Summary of the Invention

[0007] In order to overcome the shortcomings of the prior art, the present invention aims to provide a rapid preparation method for high-performance ceramic materials, which have the characteristics of high density and high mechanical properties.

[0008] The objective of this invention is achieved through the following technical solution: A method for preparing ceramic materials by ultrafast sintering coupled with an electric field and a dynamic pressure field includes the following steps: a) Ultra-rapid heating sintering After the ceramic powder is filled into the sintering mold, it is placed in a rapid hot pressing sintering equipment and sintered for a short time under vacuum conditions. The sintering mold is heated rapidly by electric current to achieve ultra-fast temperature rise.

[0009] Preferably, the ceramic powder is sieved, or the ceramic powder is mixed evenly with the sintering aid and then sieved, and then filled into the sintering mold. The mixing method is wet ball milling, dry ball milling, or ultrasonic dispersion. Since the original powder is prone to agglomeration, wet ball milling, ultrasonic dispersion, and other methods can effectively avoid powder agglomeration; a dispersant can also be added to disperse the powder by changing the surface charge state of the powder. This step is a necessary prerequisite for ensuring the uniformity of the microstructure of the final ceramic sample. Further, it is preferred that the ultrasonic frequency used for mixing the aid is 20-40 kHz, the ultrasonic time is 5-10 min, the ball milling speed is 200-600 rpm, and the ball milling time is 4-48 h.

[0010] Preferably, the sintering aid is a liquid-phase sintering aid and / or a solid-phase sintering aid. The liquid-phase sintering aid is selected from one or more of Al2O3, Y2O3, MgO, CaO, La2O3, CeO2, Nd2O3, Sm2O3, and Yb2O3. The solid-phase sintering aid is selected from at least one of B4C, AlN, BN, and C. Based on 100wt% of the total mass of the raw material powder, the total amount of the sintering aid is 0-20wt% of the total mass of the raw material, preferably 5-10wt%.

[0011] Preferably, the ceramic powder is selected from at least one of carbides, nitrides, and oxides; the carbides are selected from at least one of SiC, B4C, TiC, WC, HfC, and TaC; the nitrides are selected from at least one of Si3N4, AlN, BN, TiN, and GaN; and the oxides are selected from at least one of Al2O3, Y2O3, MgO, CaO, SiO2, and ZrO2.

[0012] Preferably, the sintering mold is a conductive mold with filling holes, the mold material is graphite or carbon-carbon composite material, and the shape of the filling holes is cylindrical or square, preferably cylindrical.

[0013] Preferably, the rapid hot pressing sintering process is selected from one of the following: spark plasma sintering (SPS), DC electric field assisted sintering, AC electric field assisted rapid sintering, pulse current assisted rapid sintering, and Joule heating.

[0014] Preferably, the sintering atmosphere is a vacuum or a protective atmosphere, wherein the protective atmosphere is selected from nitrogen, argon, or a mixture of nitrogen and argon.

[0015] In one embodiment of the present invention, after the powder filling is completed, the mold is placed in the sintering furnace cavity, a certain pressure is applied to the mold for pre-compression, and a vacuum or protective atmosphere is applied to the furnace cavity. Simultaneously, an electric field is applied to the ceramic powder through the mold. The control parameters of the electric field include voltage, current, and current waveform, and the current application method is any one of direct current, alternating current, or pulsed current. The electric field uses voltage and current as adjustment parameters, and the heating rate and sintering thermal process are controlled by adjusting the input voltage, current magnitude, and current waveform.

[0016] Preferably, the treated powder is filled into a sintering mold, and a pre-compression pressure is applied to the mold. After a protective atmosphere or vacuum is established in the furnace cavity, the heating system is started, and the temperature is rapidly increased at a rate of 100-1000 °C / min, while the pressure is increased slowly and simultaneously during the heating process. When the temperature reaches the target sintering temperature of 1500-2100 °C, the pressure is increased to 10-200 MPa. The rapid heating is achieved by electric heating through an electric field, and the electric heating method is selected from one of continuous DC heating, AC heating, or pulsed current heating.

[0017] b) Dynamic oscillating force field assisted sintering

[0018] Once the temperature reaches the target sintering temperature and the pressure stabilizes, the dynamic oscillation force field is activated, and the ceramic material is obtained after sintering.

[0019] Preferably, after the temperature reaches the target sintering temperature of 1500-2100℃ and the pressure stabilizes at 10-200 MPa, the temperature and pressure are held for 30 seconds, and then the dynamic oscillation force field is activated. During oscillation, the median pressure is set to 10-200 MPa, the amplitude is 10-50 MPa, the oscillation frequency is 0.1-100 Hz, and the oscillation holding time is 3-10 min.

[0020] Preferably, the dynamic oscillation force field is one or any two of the following: sine wave, cosine wave, square wave, and triangular wave. More preferably, the oscillation waveform of the dynamic oscillation pressure is a sine wave.

[0021] The present invention also provides ceramic materials prepared by the method, which have a relative density ≥97% and improved micro Vickers hardness.

[0022] The electric field-dynamic pressure field coupled ultrafast sintering mechanism of the present invention is as follows: (1) Regarding electric field-assisted rapid hot pressing sintering: This invention utilizes the short-time high-temperature characteristics of rapid hot pressing sintering technology, which can significantly shorten the residence time of materials in the high-temperature range, thereby effectively suppressing abnormal grain growth caused by prolonged high temperatures in traditional sintering processes, making it easier for the sintered body to maintain a fine-grained and uniform microstructure. In addition, the ultra-rapid heating allows the material system to cross multiple temperature ranges in a short period of time, making it difficult for some microstructure adjustment processes to proceed fully along the equilibrium path, thus making the sintering process exhibit more obvious non-equilibrium characteristics. Based on this non-equilibrium thermal history, the material interior is more conducive to the formation or retention of special microstructure states that are not easily obtained under conventional slow-heating sintering conditions, thereby providing a new approach to the microstructure control and performance improvement of ceramic materials.

[0023] (2) Regarding the dynamic oscillating force field assisted sintering technology: This invention uses dynamic pressure instead of traditional static pressure, which can significantly promote the elimination of pores, improve the density of the material, and change the microstructure of the ceramic sample by controlling the oscillation amplitude. Introducing dynamic pressure during the sintering process provides a new densification mechanism, including reducing particle agglomeration, inducing grain rearrangement, promoting grain boundary slip and plastic deformation, thereby accelerating the densification process. At the same time, under the non-equilibrium sintering conditions established by ultra-rapid heating, the dynamic oscillating pressure field can further enhance the dynamic response of the particle system and grain boundary regions, promote the adjustment of local contact states and the material migration process, improve the utilization efficiency of the densification driving force, and strengthen the formation and retention of non-equilibrium microstructures. In addition, dynamic pressure is also beneficial to suppress grain coarsening, strengthen grain boundaries, increase dislocation density and optimize grain boundary characteristics, thereby comprehensively improving the mechanical properties of the material.

[0024] Furthermore, the "ultra-rapid heating + dynamic oscillating pressure field" technical approach in this invention has a more significant advantage in microstructure control compared to the "slow heating + dynamic oscillating pressure field" approach. While introducing oscillation under slow heating conditions can also influence the sintering process, the longer residence time of the material in the high-temperature range makes the system more prone to evolving towards a thermodynamically stable state, leading to continuous grain growth and difficulty in effectively preserving some non-equilibrium microstructure characteristics. Therefore, the oscillation effect mainly serves as an auxiliary improvement to the conventional sintering process. In contrast, this invention significantly compresses the high-temperature treatment time through ultra-rapid heating and forms a synergistic effect with the dynamic oscillating pressure field. This not only further suppresses grain coarsening but also better induces and preserves special microstructure states that are difficult to form under conventional slow sintering conditions. Therefore, the technical advantage of this invention is not only reflected in the increased sintering speed but also in the synergistic control of the densification behavior, grain evolution process, and non-equilibrium microstructure formation mechanism of ceramic materials.

[0025] The present invention has the following beneficial effects: This invention provides a method for preparing ceramic materials. The key innovation lies in employing a sintering strategy that couples oscillating pressure with ultra-fast sintering, which to some extent alters the densification path and microstructure evolution mechanism of ceramic materials. This sintering method can simultaneously achieve densification and inhibit grain growth in a relatively short time, and is beneficial for introducing and retaining more lattice defects and special microstructures, thereby significantly improving material properties. The ceramic materials prepared using this method have a relative density ≥97% and improved micro-Vickers hardness. Attached Figure Description

[0026] To more clearly illustrate the technical solutions in the embodiments of the present invention, the accompanying drawings used in the description of the embodiments will be briefly introduced below. Obviously, the accompanying drawings described below are only some embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.

[0027] Figure 1 This is a schematic diagram of the electric field-dynamic pressure field coupled ultrafast hot pressing sintering principle described in this invention; Figure 2 The sintering process of Example 1; Figure 3 Initial powder SEM and powder particle size statistics for Example 1 and Comparative Example 1; Figure 4 The SEM images of the etched surfaces of the samples prepared in Example 1 of this invention and the particle size statistics of the ceramics prepared are shown. Figure 5 This is a diagram of the ceramic microstructure obtained in Example 1; Figure 6 The original powder SEM and powder particle size statistics for Example 3 and Comparative Example 3; Figure 7 The microstructure diagram and particle size statistics of the ceramic obtained in Example 3 are shown. Figure 8 The original powder TEM and powder particle size statistics for Example 4 and Comparative Example 4; Figure 9 The image shows the ceramic microstructure and particle size distribution obtained in Example 4. Detailed Implementation

[0028] To make the technical problems, technical solutions and advantages of the present invention clearer, a detailed description will be given below in conjunction with the accompanying drawings and specific embodiments.

[0029] Example 1

[0030] Boron carbide ceramics were prepared using B4C powder with an average grain size of 2 μm under dynamic pressure and DC electric field assisted rapid hot pressing sintering conditions. a) B4C powder with an average grain size of 2 μm was sieved and then filled into a carbon-carbon composite mold with a diameter of 20 mm, and sintered under vacuum conditions. First, a pre-compression pressure of 0.36 t was applied to the B4C powder, and then it was rapidly heated to 1900 °C at a heating rate of 700 °C / min; during the heating process, the pressure was simultaneously increased to 100 MPa.

[0031] b) Once the temperature reaches the target sintering temperature of 1900℃ and the pressure stabilizes at 100 MPa, maintain the temperature and pressure for 30 seconds, then activate the dynamic oscillation force field. Set the median pressure to 100 MPa, the amplitude to 50 MPa, the oscillation frequency to 5 Hz, and the oscillation holding time to 6 minutes.

[0032] c) After the oscillation ends, the furnace is cooled and held at 100 MPa for 1 min before the pressure is reduced to 0.36 t.

[0033] The obtained sample was polished and its properties were characterized. The relative density was 99.82% and the average grain size was 2.2 μm. The micro Vickers hardness was 41.8 GPa.

[0034] Example 2

[0035] Boron carbide ceramics were prepared using B4C powder with an average grain size of 3 μm under dynamic pressure and DC electric field assisted rapid hot pressing sintering conditions. a) B4C powder with an average grain size of 3 μm was sieved and filled into a carbon-carbon composite mold with a diameter of 20 mm, and sintered under vacuum conditions. First, a pre-compression pressure of 0.36 t was applied to the B4C powder, and then it was rapidly heated to 1800 °C at a heating rate of 500 °C / min; during the heating process, the pressure was simultaneously increased to 120 MPa.

[0036] b) Once the temperature reaches the target sintering temperature of 1800℃ and the pressure stabilizes at 120 MPa, maintain the temperature and pressure for 30 seconds, then activate the dynamic oscillation force field. Set the median pressure to 120 MPa, the amplitude to 30 MPa, the oscillation frequency to 10 Hz, and the oscillation holding time to 6 minutes.

[0037] c) After the oscillation ends, the furnace is cooled and held at 120 MPa for 1 min before the pressure is reduced to 0.36 t.

[0038] The obtained sample was polished and its properties were characterized. The relative density was 99.85% and the average grain size was 3.1 μm. The micro Vickers hardness was 40.3 GPa.

[0039] Example 3

[0040] Silicon nitride ceramics were prepared using Si3N4 powder with an average grain size of 150 nm under dynamic pressure and DC electric field assisted rapid hot pressing sintering conditions. a) Mix α-Si3N4 with Al2O3 and Y2O3 nanopowders with an average grain size of 150 nm at a ratio of m α-Si3N4 :m Al2O3 :m Y2O3 After weighing the Si3N4 powder in a 90:6:4 ratio, a slurry was prepared with ethanol. The slurry was then wet-milled in a ball mill jar for 10 hours at 350 rpm. After milling, the powder was dried and sieved. The processed powder was then filled into a 12 mm diameter graphite mold and sintered under vacuum. First, a pre-compression pressure of 0.15 t was applied to the Si3N4 powder, followed by rapid heating to 1650 °C at a heating rate of 500 °C / min; during the heating process, the pressure was simultaneously increased to 50 MPa.

[0041] b) Once the temperature reaches the target sintering temperature of 1650℃ and the pressure stabilizes at 50 MPa, maintain the temperature and pressure for 30 seconds, then activate the dynamic oscillation force field. Set the median pressure to 50 MPa, the amplitude to 25 MPa, the oscillation frequency to 3 Hz, and the oscillation holding time to 6 minutes.

[0042] c) After oscillation, the sample was cooled in the furnace and held at 50 MPa for 30 s before being unloaded to 0.15 t. The resulting sample was then polished and its properties were characterized. The relative density was 98.17%; the average grain size was 248.61 nm; and the microVickers hardness was 18.36 GPa, as measured by Archimedes' displacement method.

[0043] Example 4

[0044] Silicon carbide ceramics were prepared using SiC powder with an average grain size of 50 nm under dynamic pressure field and DC electric field assisted rapid hot pressing sintering conditions. a) Mix β-SiC with an average grain size of 50 nm with Al2O3 and Y2O3 nanopowders at a ratio of m α-SiC :m Al2O3 :m Y2O3Weighing the β-SiC nanoparticles in a 90:6:4 ratio, the β-SiC nanoparticles were first prepared into a slurry with ethanol and ultrasonically dispersed in an ice-water bath for 5 min. After removal, Al2O3 and Y2O3 nanoparticles were gradually added to the β-SiC slurry under magnetic stirring. The mixed slurry was then ultrasonically dispersed again in an ice-water bath for 5 min. The slurry was then poured into a ball mill and wet-milled for 8 h at 400 rpm. After drying, the slurry was sieved for subsequent sintering. The treated powder was then filled into a 12 mm diameter graphite mold and sintered under vacuum. A pre-pressure of 0.15 t was first applied to the SiC powder, followed by rapid heating to 1800 °C at a heating rate of 700 °C / min; the pressure was simultaneously increased to 50 MPa during the heating process.

[0045] b) Once the temperature reaches the target sintering temperature of 1800℃ and the pressure stabilizes at 50 MPa, maintain the temperature and pressure for 30 seconds, then activate the dynamic oscillation force field. Set the median pressure to 50 MPa, the amplitude to 25 MPa, the oscillation frequency to 5 Hz, and the oscillation holding time to 6 minutes.

[0046] c) After oscillation, the sample was cooled in the furnace and held at 50 MPa for 30 s before being unloaded to 0.15 t. The resulting sample was then polished and its properties were characterized. The relative density was 97.84%; the average grain size was 118.85 nm; and the microVickers hardness was 21.35 GPa, as measured by Archimedes' displacement method.

[0047] Comparative Example 1

[0048] Boron carbide ceramics were prepared using B4C powder with an average grain size of 2 μm under dynamic pressure and conventional hot-pressing sintering conditions. B4C powder with an average grain size of 2 μm was filled into a carbon-carbon composite mold with a diameter of 20 mm and sintered under vacuum. First, a pre-compression pressure of 0.36 t was applied to the B4C powder, followed by rapid heating to 1900 °C at a rate of 10 °C / min. During heating, the pressure was simultaneously increased to 100 MPa. Once the target sintering temperature of 1900 °C was reached and the pressure stabilized at 100 MPa, an oscillating force field was initiated. The median pressure was set at 100 MPa, the amplitude at 50 MPa, the oscillation frequency at 5 Hz, and the oscillation holding time at 2 h. After oscillation, the furnace was cooled, and the pressure was unloaded to 0.36 t.

[0049] The obtained sample was polished and its properties were characterized. The relative density was 98.55% and the average grain size was 3.4 μm. The micro Vickers hardness was 37.6 GPa.

[0050] Comparative Example 2

[0051] Boron carbide ceramics were prepared using B4C powder with an average grain size of 3 μm under static pressure and DC electric field-assisted rapid hot pressing sintering conditions. B4C powder with an average grain size of 3 μm was filled into a carbon-carbon composite mold with a diameter of 20 mm and sintered under vacuum conditions. First, a pre-compression pressure of 0.36 t was applied to the B4C powder, and then the B4C powder was heated to 1800 ℃ at a heating rate of 500 ℃ / min. After holding at this temperature for 30 s, the pressure was rapidly increased to 120 MPa, and the powder was held at this temperature and pressure for 7 min before being cooled in the furnace.

[0052] The obtained sample was polished and its properties were characterized. The relative density was 97.85% and the average grain size was 3.4 μm. The micro Vickers hardness was 36.9 GPa.

[0053] Comparative Example 3

[0054] Silicon nitride ceramics were prepared using Si3N4 powder with an average grain size of 150 nm under static pressure and DC electric field-assisted rapid hot pressing sintering conditions. α-Si3N4 with an average grain size of 150 nm was mixed with Al2O3 and Y2O3 nanopowders at a ratio of m α-Si3N4 :m Al2O3 :m Y2O3 After weighing the Si3N4 powder in a 90:6:4 ratio, a slurry was prepared with ethanol. The slurry was then wet-milled in a ball mill jar for 10 hours at 350 rpm. After milling, the powder was dried and sieved. The processed powder was then filled into a 12 mm diameter graphite mold and hot-pressed under vacuum. First, a pre-pressure of 0.15 t was applied to the Si3N4 powder, followed by rapid heating to 1650 °C at a heating rate of 10 °C / min. During the heating process, the pressure was simultaneously increased to 80 MPa, and the powder was held at this temperature and pressure for 2 hours before being cooled in the furnace.

[0055] The obtained sample was polished and its properties were characterized. The relative density was 97.68% and the average grain size was 938.45 nm, respectively, and the micro Vickers hardness was 16.79 GPa, as measured by Archimedes' displacement method.

[0056] Comparative Example 4

[0057] Silicon carbide ceramics were prepared using SiC powder with an average grain size of 50 nm under static pressure and DC electric field-assisted rapid hot pressing sintering conditions. β-SiC with an average grain size of 50 nm was mixed with Al2O3 and Y2O3 nanopowders at a ratio of m α-SiC :m Al2O3 :m Y2O3The β-SiC nanoparticles were first prepared into a slurry using ethanol at a ratio of 90:6:4. This slurry was then ultrasonically dispersed in an ice-water bath for 5 minutes. After removal, Al₂O₃ and Y₂O₃ nanoparticles were gradually added to the β-SiC slurry under magnetic stirring. The slurry was then ultrasonically dispersed again in an ice-water bath for 5 minutes. The slurry was then poured into a ball mill and wet-milled for 8 hours at 400 rpm. After drying, the slurry was sieved for subsequent sintering. The treated powder was then filled into a 12 mm diameter graphite mold and sintered under vacuum. A pre-pressure of 0.15 t was applied to the SiC powder, followed by rapid heating to 1800 °C at a rate of 700 °C / min. During heating, the pressure was simultaneously increased to 80 MPa, and the mixture was held at this temperature and pressure for 7 minutes before being cooled in the furnace.

[0058] The obtained sample was polished and its properties were characterized. The relative density was 96.31% and the average grain size was 368.57 nm, respectively, measured by Archimedes' displacement method. The micro Vickers hardness was 17.27 GPa.

[0059] The relative density, average grain size, and Vickers hardness of the ceramics prepared in Examples 1-4 and Comparative Examples 1-4 are shown in Table 1.

[0060] Table 1

[0061] As shown in Table 1, Examples 1 and 2 of this invention employ electric field-dynamic pressure field coupled ultra-fast hot pressing sintering. The B4C ceramics prepared exhibit a relative density of not less than 99.5% and a micro Vickers hardness exceeding 40 GPa, demonstrating excellent densification and mechanical properties. Further comparison of Example 1 and Comparative Example 1 reveals that Comparative Example 1 did not introduce a DC electric field to assist rapid sintering, but only introduced a dynamic pressure field to assist in the sintering of B4C. The average grain size of the sample prepared by this control process reached 3.4 μm. Comparative Example 2 and Comparative Example 2 show that the comparative example did not introduce a dynamic pressure field to assist in sintering, but only used rapid hot pressing to sinter B4C under vacuum conditions. The relative density of the sample prepared by this control process was significantly lower, and the hardness was generally lower than that of the corresponding example samples. The overall mechanical properties of Comparative Examples 1 and 2 are significantly deteriorated compared to Examples 1 and 2.

[0062] Comparing the experimental data of Example 3 and Comparative Example 3 (Si3N4), it can be seen that: in Comparative Example 3, which uses conventional hot pressing sintering, grain growth is significant, and α-Si3N4 almost completely transforms into β-Si3N4; while Example 3 uses electric field-dynamic pressure field coupled ultra-fast hot pressing sintering, which achieves a density similar to that of Comparative Example 3 while effectively suppressing grain growth, with an α-Si3N4 retention rate as high as 77%, and a hardness significantly higher than that of Comparative Example 3.

[0063] Further comparative studies on silicon carbide (SiC) ceramic systems show that: Comparative Example 4, prepared by rapid hot pressing sintering under a static pressure field at 1800℃, has a density of 96.3% and a hardness of only 17.27 GPa; Example 4, using an electric field-dynamic pressure field coupled ultra-fast hot pressing sintering process, achieves a density of 97.8% and a hardness of 21.35 GPa at the same sintering temperature (1800℃), exhibiting superior densification effect and mechanical properties.

[0064] The following test results verify that the present invention successfully prepared high-performance ceramic materials with fine grains through the process route of "electric field-dynamic pressure field coupled ultra-fast sintering". Figure 1 The mechanism diagram of the electric field-dynamic pressure field coupled ultra-fast sintering equipment is shown. Ultra-fast heating is achieved by energizing the mold through both ends of the electrodes, and the temperature inside the mold is uniform. The hydraulic system provides a stable dynamic pressure field.

[0065] Figure 2 The sintering process of Example 1 is shown. Figure 2 In (a), the T curve represents the temperature change process during sintering, the F curve represents the pressure change process during sintering, and the D curve represents the sample displacement change process during sintering. Through the displacement curves, it can be observed that the displacement slowly increases during the dynamic pressure stage, indicating that dynamic pressure helps the densification process of the sample. Figure 2 (b) is a partial waveform diagram of the pressure and displacement change curves during the oscillation phase in (a).

[0066] Figure 3 The original powder microstructure and particle size distribution statistical results of Example 1 are shown, where (a) is the original powder morphology; (b) is the particle size distribution statistical results of the powder in (a), indicating that the average particle size is 1.96 μm.

[0067] Figure 4 The etching morphology and grain size distribution of the B4C polished surface after sintering in Example 1 are shown. The average grain size after sintering is 2.16 μm, and the grains only grow by 10%. Compared with Comparative Example 1 in Table 1, where the grains grew by 76% before and after sintering, this shows that the method of the present invention can effectively suppress grain growth.

[0068] Figure 5 The microstructure diagram of the ceramic material in Example 1 is shown. It can be seen that the ceramic prepared by the process route provided by the present invention has a large number of stacking faults, which is also the reason for the excellent performance of the B4C ceramic prepared by the present invention.

[0069] Figure 6The microstructure and particle size distribution of the original powder in Example 3 (Si3N4 ceramic system) are shown. (a) shows the original powder morphology; (b) shows the particle size distribution of the powder in (a), indicating that the average grain size is 150.47 nm.

[0070] Figure 7 The microstructure and particle size distribution statistics of the ceramic obtained in Example 3 are shown, where (a) is the original powder morphology; (b) is the particle size distribution statistics of the powder in (a), indicating that the average grain size is 48.70 nm. (Comparison) Figure 6 and Figure 7 As can be seen, the α-Si3N4 grains hardly underwent a phase transformation and remained in the α-Si3N4 phase; and the grains in Example 3 grew by only 65% ​​before and after sintering, while Comparative Example 3 in Table 1 showed that the grains grew by 525% before and after sintering, which is much greater than that in Example 3.

[0071] Figure 8 The original powder microstructure and particle size distribution of Example 4 (SiC ceramic system) are shown in the figure. (a) shows the original powder morphology, which shows that there are a large number of stacking faults in the ceramic grains of Example 4; (b) shows the particle size distribution of the powder in Figure (a), which shows that the average particle size is 118.85 nm. Figure 9 The microstructure and grain size distribution statistics of the ceramic obtained in Example 4 are presented. Calculations show that the grain growth in Example 4 was 144% before and after sintering, compared to 657% in Comparative Example 4. The grains in Example 4 showed almost no significant growth before and after sintering.

[0072] In summary, this invention provides a method for preparing high-performance ceramic materials by ultra-fast sintering coupled with an electric field and a dynamic pressure field. The core of this method lies in the dual innovative strategy of "electric field-dynamic pressure field coupled ultra-fast sintering." In the early stages of sintering, the technical advantage of "rapid hot pressing" significantly shortens the high-temperature holding time, thereby effectively inhibiting grain growth. In the middle and later stages of sintering, the introduction of a "dynamic oscillating force field" alters the densification mechanism of the ceramic material, causing a large number of micro-defects to be generated during sintering, thus achieving a significant improvement in material properties. The ceramic material prepared using this method exhibits significantly improved density (≥97%), a significantly enhanced micro-Vickers hardness, and almost no grain growth.

[0073] The above description is merely a specific embodiment of the present invention, but the scope of protection of the present invention is not limited thereto. Any variations or substitutions that can be easily conceived by those skilled in the art within the technical scope disclosed in the present invention should be included within the scope of protection of the present invention. Therefore, the scope of protection of the present invention should be determined by the scope of the claims.

Claims

1. A method for preparing ceramic materials by ultrafast sintering coupled with an electric field and a dynamic pressure field, characterized in that, Includes the following steps: a) After filling the ceramic powder into the sintering mold, it is placed in a rapid hot pressing sintering equipment and sintered for a short time under vacuum conditions. The sintering mold is heated rapidly by current to achieve ultra-rapid temperature rise. b) Once the temperature reaches the target sintering temperature and the pressure stabilizes, the dynamic oscillation force field is activated, and the ceramic material is obtained after sintering.

2. The method for preparing ceramic materials by ultrafast sintering coupled with an electric field and dynamic pressure field according to claim 1, characterized in that, In step a), the ceramic powder is sieved, or the ceramic powder is mixed evenly with the sintering aid and then sieved, and then filled into the sintering mold together.

3. The method for preparing ceramic materials by ultrafast sintering coupled with an electric field and dynamic pressure field according to claim 2, characterized in that, In step a), the mixing method is wet ball milling, dry ball milling or ultrasonic dispersion. Preferably, the ultrasonic frequency used for mixing the additive is 20-40 kHz, the ultrasonic time is 5-10 min, the ball milling speed is 200-600 rpm, and the ball milling time is 4-48 h.

4. The method for preparing ceramic materials by ultrafast sintering coupled with an electric field and a dynamic pressure field according to claim 2, characterized in that, In step a), the sintering aid is a liquid-phase sintering aid and / or a solid-phase sintering aid. The liquid-phase sintering aid is selected from one or more of Al2O3, Y2O3, MgO, CaO, La2O3, CeO2, Nd2O3, Sm2O3, and Yb2O3. The solid-phase sintering aid is selected from at least one of B4C, AlN, BN, and C. Based on 100wt% of the total mass of the raw material powder, the total amount of the sintering aid is 0-20wt% of the total mass of the raw material, preferably 5-10wt%.

5. The method for preparing ceramic materials by ultrafast sintering coupled with an electric field and dynamic pressure field according to claim 1, characterized in that, In step a), the sintering mold is a conductive mold with filling holes, the mold material is graphite or carbon-carbon composite material, and the shape of the filling holes is cylindrical or square.

6. The method for preparing ceramic materials by ultrafast sintering coupled with an electric field and dynamic pressure field according to claim 1, characterized in that, In step a), the rapid hot pressing sintering process is selected from one of the following: spark plasma sintering (SPS), DC electric field assisted sintering, AC electric field assisted rapid sintering, pulse current assisted rapid sintering, and Joule heating. And / or, the sintering atmosphere is a vacuum or a protective atmosphere, wherein the protective atmosphere is selected from nitrogen, argon or a mixture of nitrogen and argon.

7. The method for preparing ceramic materials by electric field-dynamic pressure field coupled ultrafast sintering according to claim 6, characterized in that, In step a), the processed powder is filled into the sintering mold. After a protective atmosphere or vacuum is established in the furnace cavity, the heating system is started and the temperature is rapidly increased at a rate of 100-1000 ℃ / min, while the pressure is increased simultaneously during the heating process. When the temperature reaches the target sintering temperature of 1500-2100℃, the pressure is increased to 10-200 MPa. And / or, the rapid heating is achieved by electric heating through an electric field, and the electric heating method is selected from one of continuous DC heating, AC heating or pulse current heating.

8. The method for preparing ceramic materials by electric field-dynamic pressure field coupled ultrafast sintering according to claim 7, characterized in that, In step b), after the temperature reaches the target sintering temperature of 1500-2100℃ and the pressure stabilizes at 10-200 MPa, the temperature and pressure are maintained for 30 s, and then the dynamic oscillation force field is activated. During the oscillation, the median pressure was set to 10-200 MPa, the amplitude to 10-50 MPa, the oscillation frequency to 0.1-100 Hz, and the oscillation holding time to 3-10 min.

9. The method for preparing ceramic materials by ultrafast sintering coupled with an electric field and dynamic pressure field according to claim 8, characterized in that, In step b), the dynamic oscillation force field is one or any two of the following: sine wave, cosine wave, square wave, and triangular wave. Preferably, the oscillation waveform of the dynamic oscillation pressure is a sine wave.

10. The ceramic material prepared by the method according to any one of claims 1 to 9, characterized in that, Its relative density is ≥97%.